One-stage cementless revision arthroplasty for infected hip replacements - Yoo, Jeong Joon (Springer-Verlag, 2008)
We hypothesised that one-stage cementless revision hip arthroplasty may have advantages and a role in the treatment of selected patients with an infected hip replacement. We retrospectively reviewed all patients with an infected hip replacement treated with one-stage revision using cementless implants. Twelve patients were reviewed and followed up for at least three years (average: 7.2 years, range: 3.3–11.3 years) postoperatively. One recurrence of infection and one aseptic stem loosening were detected during follow-up. Grafted bone, which was used in eight patients, appeared to have united to host bone in all patients. The success rate of treatment was 83.3% when infection recurrence or component loosening were regarded as failure. One-stage revision hip arthroplasty using cementless implants appears to have a role in the treatment of carefully selected patients with an infected hip replacement if meticulous débridement is performed and appropriate antibiotics are properly used.